Teachers’ Teaching Preparation Towards Their Real Teaching Practice in EFL Classroom (RETAIN, 2018)
AbstrakDalam kegiatan belajar mengajar, seorang guru harus menyiapkan RPP dan materi yang akan diajarkan kepada siswanya. RPP yang disiapkan akan bermanfaat untuk guru ketika dia melakukan kegiatan mengajar di dalam kelas. RPP harus jelas dan detail karena di dalamnya berii tentang kompetensi dasar, indikator pencapaian kompetensi, tujuan pembelajaran, materi yang diajarkan hingga pedoman penilaian yang akan digunakan gu4ru. Dalam hal ini, RPP menjadi pedoman bagi guru dalam melakukan kegiatan pembelajaran di kelas. Penelitian ini membedah kesesuaian isi dari RPP guru serta implementasinya dalam kegiatan mengajar guru di kelas. Penelitian ini menggunakan metode kualitatif dalam proses mengumpulkan data dan menjawab rumusan masalah. Kesimpulan dari penelitian ini adalah RPP yang digunakan guru kurang update dan kurang detail. Sedangkan implementasinya berbeda dengan apa yang mereka buat di RPP dan beberapa guru harus mengubah keseluruhan strategi mengajar dan keseluruhan kegiatan pembelajaran di kelas meskipun kegiatan pembelajaran berlangsung aktif an kondusif.Kata Kunci : RPP, kegiatan mengajarAbstractIn teaching and learning activities, a teacher must prepare lesson plan and materials to be taught to his students. The lesson plan will be useful for teachers when they do real teaching practice in the classroom. The lesson plan should be clear and detailed because it contains basic competence, indicator of competence achievement, learning objectives, material to be taught and assessment guidelines. In this case, the lesson plan becomes a guide for teachers in conducting classroom learning activities. This study dissects the content of the teachers lesson plan as well as its implementation in real teaching practice in the classroom. This study used qualitative methods in the process of collecting data and answering the research questions. The conclusion of this research is lesson plans used by teachers were less updated and less detailed. While the implementation of the lesson plan in the classroom was different from what they designed in the lesson plan and some teachers have to change the overall teaching strategy and learning activities in the classroom even though the learning activities are active and conducive..Keywords: lesson plan, real teaching practice.